Do men and women arrive, stay, and respond differently to cognitive behavior group therapy for social anxiety disorder?. (May 2019) - Asher, Maya; Hermesh, Haggai; Gur, Shay; Marom, Sofi; Aderka, Idan
Highlights: We examined gender differences in treatment seeking individuals with SAD. Women reported greater pretreatment severity of social anxiety. Men dropped out of treatment to a greater extent than women. Women demonstrated greater improvement during treatment compared to men. Abstract: This study examined gender differences in a large sample ( n = 1010) of individuals who sought cognitive behavioral group therapy (CBTG) for social anxiety disorder (SAD) in an outpatient clinic. Specifically, we examined gender differences in pretreatment clinical severity, treatment seeking, attrition, and response to treatment. Findings indicated that women demonstrated greater pretreatment severity of SAD compared to men. However, we found evidence for a heightened proclivity of men to seek treatment. Men also dropped out of treatment to a greater extent than women, and women responded to treatment more than men. The findings are discussed in the context of the SAD literature, of genetic vulnerability factors and of gender theories. Identifying and understanding gender differences in SAD, and specifically in treatment for SAD, may have important implications for both assessment and treatment of the disorder.